2018
DOI: 10.3389/fnagi.2018.00204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphodiesterase-4 Reverses Aβ-Induced Memory Impairment by Regulation of HPA Axis Related cAMP Signaling

Abstract: Beta amyloid peptides (Aβ) are found to be associated with dysfunction of hypothalamic-pituitary-adrenal axis (HPA axis) that leads to memory and cognitive deficits in patients with Alzheimer's disease (AD). Phosphodiesterase 4 (PDE4) inhibitors increase the intracellular cAMP activities, which may ameliorate cognitive deficits associated with AD. However, it remains unclear whether PDE4-mediated reversal of cognitive impairment in mouse model of AD is related to HPA axis and downstream cAMP-dependent pathway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…However, PDE4 inhibitors may cause severe nausea and vomiting, particularly at the high doses necessary for therapeutic benefit (Robichaud et al, 2002; Azzouni and Samra, 2011), while PDE2 presence was plentiful in the limbic nervous system (cortex and hippocampus) and the adrenal cortex (Van Staveren et al, 2003), which are areas predominantly relevant to HPA axis regulation and cognitive processes, while it does not cause nausea and vomiting. Moreover, some studies suggest that PDE2 inhibition reverses chronic stress- or Aβ-induced memory deficits (van Donkelaar et al, 2008; Reneerkens et al, 2013), which are consistent with our previous studies suggesting that PDE2 inhibition could reverse memory impairment and chronic stress-induced learning via the HPA axis’ regulation and the downstream signaling (Xu et al, 2015, 2018). The present study expanded upon our previous studies and demonstrated that Bay 60-7550 at doses of 0.5, 1.0, and 3.0 mg/kg daily for 14 days was able to protect animals against Aβ1–42-induced spatial memory deficits, as mice treated with Bay 60-7550 learned at a faster rate in both the training (acquisition of memory) and test sessions (1 and 24 h after the training session), i.e., ameliorated short- and long-term memory consolidation and retrieval in the water maze test.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, PDE4 inhibitors may cause severe nausea and vomiting, particularly at the high doses necessary for therapeutic benefit (Robichaud et al, 2002; Azzouni and Samra, 2011), while PDE2 presence was plentiful in the limbic nervous system (cortex and hippocampus) and the adrenal cortex (Van Staveren et al, 2003), which are areas predominantly relevant to HPA axis regulation and cognitive processes, while it does not cause nausea and vomiting. Moreover, some studies suggest that PDE2 inhibition reverses chronic stress- or Aβ-induced memory deficits (van Donkelaar et al, 2008; Reneerkens et al, 2013), which are consistent with our previous studies suggesting that PDE2 inhibition could reverse memory impairment and chronic stress-induced learning via the HPA axis’ regulation and the downstream signaling (Xu et al, 2015, 2018). The present study expanded upon our previous studies and demonstrated that Bay 60-7550 at doses of 0.5, 1.0, and 3.0 mg/kg daily for 14 days was able to protect animals against Aβ1–42-induced spatial memory deficits, as mice treated with Bay 60-7550 learned at a faster rate in both the training (acquisition of memory) and test sessions (1 and 24 h after the training session), i.e., ameliorated short- and long-term memory consolidation and retrieval in the water maze test.…”
Section: Discussionsupporting
confidence: 90%
“…Aβ deposition in brain zones such as the prefrontal cortex and hippocampus is considered an early or late affair in the procedure of AD, which is involved in the worsening in memory processes and learning (Wang et al, 2016). Our previous studies suggested that the PDE4 inhibitor rolipram reversed Aβ1–42-induced memory impairment, as evidenced by increased crossing numbers and shorter latency to reach the target zone where the platform was removed in the test session (Xu et al, 2018). However, PDE4 inhibitors may cause severe nausea and vomiting, particularly at the high doses necessary for therapeutic benefit (Robichaud et al, 2002; Azzouni and Samra, 2011), while PDE2 presence was plentiful in the limbic nervous system (cortex and hippocampus) and the adrenal cortex (Van Staveren et al, 2003), which are areas predominantly relevant to HPA axis regulation and cognitive processes, while it does not cause nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, the dysfunction of synaptic plasticity appears before A β plaque formation and contributes significantly to AD pathogenesis. Intracerebroventricular microinjection of A β can induce cognitive dysfunction, and it is also a common AD animal model to examine the effect of A β on synaptic plasticity [4446]. In the present study, we aimed to examine the effects of HLJDD and its modification on synaptic plasticity, so we chose the A β 1-42 oligomer-induced AD model for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive secretion of glucocorticoids weakens the negative regulatory feedback of the pituitary gland and the hy-pothalamus, leading to the regulatory dysfunction of the HPA axis (Nichols et al, 2001). This series of regulatory dysfunctions ultimately results in uncontrolled feedback (Xu et al, 2018). The MR and GR are nuclear transcription factors expressed in the hippocampus that exert various biological effects upon activation (Dai et al, 2018;Keller-Wood, 2015).…”
Section: Discussionmentioning
confidence: 99%